(untitled) (KULT_online, 2015)
With her dissertation thesis Kultur als Menschenrecht? Ambivalenzen kollektiver Rechtsforderungen Janne Mende enters a political-science debate that has always been controversial. She examines the theory and empiricism of collective and cultural human rights, especially the case of indigenous rights, based on qualitative and interpretative content analysis. Following Mende, collective cultural human rights may support individual human rights or undermine them – depending on the underlying notions of culture and identity, as well as their (implicit) normative standards.